Education System Control and Maintenance Mechanism - Makmur Syukri; Fachrudin Azmi; Nurul Annisa Khaidir; Adinda Suciyandhani (Universitas Muhammadiyah Enrekang, 2022)
The role of education in national development understands the meaning of development is a change towards progress and modernity, then education is an absolute requirement in development, the main role of development in education. This article uses the literature study method or what is commonly called literature study. This research was conducted by collecting data from various references through several books, magazines related to the aim of revealing various theories related to the problem being faced or studied.